The macroeconomic impact of euro area labour market reforms: Evidence from a narrative panel VAR - Gerhard Rünstler (European Central Bank (ECB), 2021)
Using new quarterly narrative evidence, this paper examines the macroeconomic impact of reforms of unemployment benefits (UB) and employment protection legislation (EPL) in the euro area from a Bayesian narrative panel VAR. The approach complements existing micro-econometric evidence by aligning short- and mediumterm effects in a unified framework and assessing state dependencies. Liberalising reforms result in temporary wage declines and highly persistent increases in economic activity and employment. In contrast to UB reforms, the effects of EPL reforms on employment emerge only gradually.
Keywords: E32; J08; O43; 330; Employment Protection Legislation; Unemployment Benefits; Narrative Identification; Discriminant Regression